2023
DOI: 10.7554/elife.81892
|View full text |Cite|
|
Sign up to set email alerts
|

Antisense oligonucleotide therapy rescues disturbed brain rhythms and sleep in juvenile and adult mouse models of Angelman syndrome

Abstract: UBE3A encodes ubiquitin protein ligase E3A, and in neurons its expression from the paternal allele is repressed by the UBE3A antisense transcript (UBE3A-ATS). This leaves neurons susceptible to loss-of-function of maternal UBE3A. Indeed, Angelman syndrome, a severe neurodevelopmental disorder, is caused by maternal UBE3A deficiency. A promising therapeutic approach to treating Angelman syndrome is to reactivate the intact paternal UBE3A by suppressing UBE3A-ATS. Prior studies show that many neurological phenot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Early preclinical UBE3A gene therapy trials in mice showed efficacy, but only with very early treatment, before the second day of life (reviewed in supplemental files of study by Lee et al 9 ). Here Lee and colleagues 9 used a novel gene therapy approach and show partial restoration of function with antisense oligonucleotide gene knockdown approaches in juvenile , and to a lesser extent in adult mice engineered with maternal UBE3A deficiency.…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations
“…Early preclinical UBE3A gene therapy trials in mice showed efficacy, but only with very early treatment, before the second day of life (reviewed in supplemental files of study by Lee et al 9 ). Here Lee and colleagues 9 used a novel gene therapy approach and show partial restoration of function with antisense oligonucleotide gene knockdown approaches in juvenile , and to a lesser extent in adult mice engineered with maternal UBE3A deficiency.…”
Section: Commentarymentioning
confidence: 99%
“…Early preclinical UBE3A gene therapy trials in mice showed efficacy, but only with very early treatment, before the second day of life (reviewed in supplemental files of study by Lee et al 9 ). Here Lee and colleagues 9 used a novel gene therapy approach and show partial restoration of function with antisense oligonucleotide gene knockdown approaches in juvenile , and to a lesser extent in adult mice engineered with maternal UBE3A deficiency. As the paternal copy of UBE3A is repressed by a specific endogenous antisense sequence (UBE3A-ATS), genetic restoration of the paternal copy through exogenous antisense oligonucleotides (ASOs) targeting UBE3A-ATS is possible; this approach was adopted by Lee and colleagues.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are not many studies that dig deeper into the cognitive issues, sleep or epilepsy-related brain activity (as measured with EEG) that are known to be affected in this mouse model. Now, in eLife, Mingshan Xue and colleagues from Baylor College of Medicine and Ionis Pharmaceuticals – including Dongwon Lee, Wu Chen, Heet Naresh Kaku and Xinming Zhuo as first authors – report on the use of an ASO to rescue the characteristic EEG pattern and disordered sleep observed in a mouse model of Angelman syndrome ( Lee et al, 2023 ).…”
mentioning
confidence: 99%